“EL ABUSO DE LA PRISIÓN PREVENTIVA Y EL HACINAMIENTO CARCELARIO” - Ordoñez Rodríguez, Jefferson Paul (2025)
The objective of this research work is to analyze the excessive use of pretrial detention and prison overcrowding in Ecuador, due to the fact that in recent years the most important and worrisome social problem in the country is the number of people deprived of liberty in prisons, which is why we seek to analyze other noncustodial precautionary measures that have the same effect and help the process to be carried out effectively. In order to determine the above, this study was descriptive, with a quantitative approach. The SNAI reports corroborate the above mentioned, since there is a significant percentage of overcrowding in prisons due to the misuse of pretrial detention, and since this is an ultimo ratio measure, it is evident that it is the measure most used by the administrators of justice. This is why the rulings of the National Court of Justice were analyzed to demonstrate in which situations the proper application of pretrial detention is based, since it should not be generalized. The results show that, in our country, there is an excessive use of pretrial detention, important aspects such as the severity of the crime are not taken into account, the administrators of justice have generalized pretrial detention as the only precautionary measure.